2015
DOI: 10.4102/phcfm.v7i1.746
|View full text |Cite
|
Sign up to set email alerts
|

Familial and socio-economic correlates of somatisation disorder

Abstract: BackgroundSomatisation disorder can result from an interplay between suboptimal family environment and socio-economic deprivation, which enhances the underlying cognitive tendency for this disorder. There are pertinent familial and socio-economic factors associated with this disorder, but research addressing this is sparse.Aim and settingThe study aims to evaluate family and socio-economic factors that are associated with somatisation disorder amongst patients presenting to the Family Medicine clinic, Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
0
10
2
Order By: Relevance
“…Further, epidemiological studies of children and adolescents conducted in India found higher prevalence rates of hysteria [ 12 ] compared with western countries. In a literature study, we also found that youngers, the female gender, rural settings, low education levels, low socioeconomic statuses, marital status, having a family member with the disease, and childhood sexual abuse are associated with an increased risk of hysteria [ 13 15 ]. Kokota et al showed that hysteria may result in significant social, economic, and health burdens in children and adolescents [ 8 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, epidemiological studies of children and adolescents conducted in India found higher prevalence rates of hysteria [ 12 ] compared with western countries. In a literature study, we also found that youngers, the female gender, rural settings, low education levels, low socioeconomic statuses, marital status, having a family member with the disease, and childhood sexual abuse are associated with an increased risk of hysteria [ 13 15 ]. Kokota et al showed that hysteria may result in significant social, economic, and health burdens in children and adolescents [ 8 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Schlarb et al (2017) found somatic complaints in 23.5% of university students. Somatic symptoms directly affect quality of life (Ammati et al, 2019), life satisfaction (Parletta et al, 2016), marital discord, financial problems and social status (Obimakinde et al, 2015) and educational achievement (Hiller et al, 2006). As most of the patients (70%) are women (Obimakinde et al, 2015) and youth (Eliasen et al, 2016), female students are more likely to be affected.…”
mentioning
confidence: 99%
“…Somatic symptoms directly affect quality of life (Ammati et al, 2019), life satisfaction (Parletta et al, 2016), marital discord, financial problems and social status (Obimakinde et al, 2015) and educational achievement (Hiller et al, 2006). As most of the patients (70%) are women (Obimakinde et al, 2015) and youth (Eliasen et al, 2016), female students are more likely to be affected. The literature indicates that stressful life events and especially childhood trauma, have particular importance in the development of somatic symptoms (Elklit and Christiansen, 2009; Nijenhuis et al, 2001; Sadeghi et al, 2017; Waller et al, 2001).…”
mentioning
confidence: 99%
“…A number of them examined the physical manifestations of mental illnesses. In psychiatric disorders such as major depression and somatization, headache was a prominent complaint (7,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…They frequently describe contextual symptoms-which, despite their strangeness, may resemble real diseases-using impressionistic language. The condition is best comprehended in relation to "illness" behavior, which conceals an underlying mental illness and only shows up as somatic symptoms (7).…”
Section: Introductionmentioning
confidence: 99%